Antisite Defects in Sol‐Gel‐Synthesized LiFePO4 at Higher Temperature: Effect on Lithium‐Ion Diffusion. Issue 22 (11th September 2018) - Raj, Hari; Rani, Sonia; Sil, Anjan
Abstract: In the present work, the study of atomic defects in LiFePO4 is achieved by Rietveld refinements. Several LiFePO4 samples are synthesized by using a sol‐gel process with varying calcination times and argon flow rates. Quantitative analysis of XRD patterns through Rietveld refinements confirms 2 % antisite defects in the LiFePO4 sample. However, for the first time, we have observed antisite defects in LiFePO4 prepared through a sol‐gel process at a higher temperature of 700 °C. Two samples identified as LFP−A and LFP−B are further studied by electrochemical analysis and electrochemical impedance spectroscopy to examine the effect of the antisite defects on the electrochemical performances and Li‐ion diffusion of LiFePO4 . Sample LFP−B with 2 % antisite defects shows, at 0.1 C rate, a lower discharge capacity of 138 mAh g −1 as compared to 150 mAh g −1 for LFP−A. LFP−B also shows shorter cycle life as well as rate capability at all of the C rates studied. Li‐ion diffusion coefficients of LFP−A and LFP−B in initially prepared electrodes are found to be 1.669×10 −13 and 1.198×10 −13 cm 2 s −1, respectively, whereas the diffusion coefficients after 200 cycles are 0.968×10 −13 and 0.436×10 −13 cm 2 s −1, respectively. Abstract : Hot defects : To examine the possibilities of antisite defect formation at higher temperatures, the antisite defects in LiFePO4 prepared by using a sol‐gel process are studied at 700 °C with varying calcination time and argon gas flow. The antisite defects are observed by Rietveld refinements and their effect on performance of LiFePO4 is determined by using electrochemical analysis and electrochemical impedance spectroscopy.